Protest Inc. the corporatization of activism - Dauvergne, Peter; LeBaron, Genevieve (Polity, 2014)
Mass protests have raged since the global financial crisis of 2008. Across the world students and workers and environmentalists are taking to the streets. Discontent is seething even in the wealthiest countries, as the world saw with Occupy Wall Street in 2011. Protest Inc. tells a disturbingly different story of global activism. As millions of grassroots activists rally against capitalism, activism more broadly is increasingly mirroring business management and echoing calls for market-based solutions. The past decade has seen nongovernmental organizations partner with oil companies like ExxonMobil, discount retailers like Walmart, fast-food chains like McDonald's, and brand manufacturers like Nike and Coca-Cola. NGOs are courting billionaire philanthropists, branding causes, and turning to consumers as wellsprings of reform... Political and socioeconomic changes are enhancing the power of business to corporatize activism, including a worldwide crackdown on dissent, a strengthening of consumerism, a privatization of daily life, and a shifting of activism into business-style institutions... -- Publisher's description.